Efeito da hemodi??lise na colapsabilidade das vias a??reas superiores em pacientes com doen??a renal cr??nica - Fons??ca, Nina Teixeira (2015)
Introduction: Currently, chronic kidney disease (CKD) is one of the most serious public health problems, becoming a global epidemic. It is also known that the volume of the rostral fluid displaced during the night, from the lower limbs is associated with increased neck circumference and severity of obstructive sleep apnea (OSA) in CKD patients undergoing hemodialysis (HD). Objectives: To determine the prevalence of excessive daytime sleepiness, the degree of collapsibility of the upper airways (UA) through the negative expiratory pressure (NEP) test in patients with CKD undergoing HD. Methods: A cross-sectional clinical study involving patients with CKD undergoing HD. It used the Epworth Sleepiness Scale and held the NEP test before and after the performance of the HD sessions. Results: It was observed that 70% of CKD patients undergoing HD exhibit excessive daytime sleepiness. The mean circumference of the neck pre dialysis was 38.60 ?? 4.32 cm whereas after dialysis was 37.92 ?? 3.89 cm and the weight of the pre hemodialysis patients had an average of 72.4 ?? 21 15 kg and 70.64 ?? 21.21 kg after hemodialysis. The average value V0,2 was 19.98 ?? 11.77% before dialysis and 28.60 ?? 21.98% after dialysis. Conclusion: Patients with CKD undergoing HD have excessive daytime sleepiness and increased expiratory flow after the NEP test. The NEP test can be stated as intervention assessment tool along the upper airway in the direction of increased expiratory flow.